Perkembangan dan Kontribusi Alumni Mesir Terhadap Pendidikan di Indonesia - Nawazir, Safrudin; Iswantir, Iswantir (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This study aims to determine the development and contribution of Egyptian alumni to education in Indonesia. The method used in this research is research library (literature review). The results of the study show that: 1) Al-Azhar Egyptian alumni in various regions have a culturalist, synergistic, active, participatory and sustainable role, 2) There is a balanced continuity as indicated by the collaboration between the roles of "ulama" (scholars) and "umara" (government) in a cultural approach, 3) socializing the vision and mission of Islamic moderation from the institution where they study.